Alexei Scheludko (1920-1995): Bibliography [In Bulgarian] - B.V. Toshev (University of Sofia, 2010)
All publications, written by Prof. Dr. Alexei Scheludko (1920-1995), are listed. Prof. Scheludko, f. head of the Department of Physical Chemistry, University of Sofia, and an active member of the Bulgarian Academy of Sciences, is a founder of the scientific school of colloid science in Bulgaria. He is among the most eminent Bulgarian scholars.